Impact of counselling provision in primary schools on child and adolescent mental health service referral rates: a longitudinal observational cohort study. Issue 2 (2nd November 2021) - Grant, Claire; Blackburn, Ruth; Harding, Duncan; Golden, Sarah; Toth, Katalin; Scott, Stephen; Ford, Tamsin; Downs, Johnny
Abstract : Background: In the United Kingdom, schools play an increasingly important role in supporting young peoples' mental health. While there is a growing evidence base to support the effectiveness of school‐based interventions, less is known about how these provisions impact on local Child and Adolescent Mental Health Service (CAMHS) referral rates. There is a concern that an increase in school‐based provision might lead to an increase in CAMHS referrals and overwhelm services. We aimed to examine the longitudinal association between Place2Be counselling provision in primary schools on CAMHS referral rates in South London. Method: This was a retrospective cohort study using linked data from the National Pupil Database (NPD) and CAMHS referrals to the South London and Maudsley's NHS Foundation Trust (SLaM) identified through the Clinical Record Interactive Search (CRIS) tool. The cohort included a total of 285 state‐maintained primary schools in four London boroughs for the academic years of 2007–2012. During the study period, 23 of these schools received school‐based mental health provision from Place2Be. The primary outcome was the incident rate ratio (IRR) of school‐level accepted CAMHS referrals in 2012/13 in schools with, or without, Place2Be provision. Results: There was no significant association between elevated rates of CAMHS referral and Place2Be provision, even after comprehensive adjustment for school‐level and pupil characteristics (IRR 0.91 (0.67–1.23)). School‐level characteristics, including higher proportion of white‐British pupils (IRR 1.009 (1.002–1.02)), medical staff ratio (IRR 6.49 (2.05–20.6)) and poorer Ofsted school inspection ratings (e.g. IRR 1.58 (1.06–2.34) for 'Requires Improvement' vs. 'Outstanding') were associated with increased CAMHS referral rates. Conclusions: Place2Be provision did not result in increased specialist mental health referrals; however, other school‐level characteristics did. Future research should investigate pupils' Place2Be clinical outcomes, as well the outcomes of individuals referred to CAMHS to better understand which needs are being met by which services.